COMPANY PERFORMANCE AND ESG DISCLOSURE: DOES COUNTRY GOVERNANCE MATTER? (EVIDENCE FROM SOUTHEAST ASIA) - Prasetyo, Doni Iwan; Y Anni Aryani (Jurnal Bisnis dan Keuangan, 2024)
This study aims to examine the effect of ESG disclosure on company performance and to analyze the moderating effect of country governance on the relationship between ESG and company performance. The study population comprises real estate companies operating in five Southeast Asian countries: Indonesia, Malaysia, the Philippines, Singapore, and Thailand (ASEAN-5). The findings reveal that ESG disclosure negatively affects firm performance, highlighting a divergence from the increasing global emphasis on sustainability issues. This indicates that Southeast Asian stakeholders may still undervalue the importance of investments in ESG-related areas. However, the study also finds that good national governance significantly moderates this relationship, mitigating the adverse effects of ESG disclosure on firm performance. This underscores effective governance's crucial role in enhancing ESG practices' benefits. The research provides valuable insights for policymakers and business leaders in the region, emphasizing the need for improved governance structures to support sustainable business practices.